Breeding report of a new late-ripening and self-fruitful sweet cherry cultivar Changhuazixia - WU Yaqin; CHENG Hehe; LI Yusheng; WU Yongjie; YAN Zhuo; WANG Xumin; JI Xinmei; ZHAO Yanhua; CHEN Long (Guoshu xuebao)
Changhuazixia is a newly released late-ripening sweet cherry cultivar developed through artificial hybridization between Hongdeng and Stella at the Changli Institute of Pomology, Hebe Academy of Agriculture and Forestry Science. Hybrid seeds were selected by embryo rescue. In 2002, over 500 seedling seeds of Hongdeng × Stella were collected through hybridization pollination, among which 365 hybrid seedlings were obtained using embryo rescue technology in 2002. Among them, HS219 was first selected in 2009 for its big fruit size and hard flesh. From 2009 to 2010, the fruiting traits of HS219 were identified by the self-pollination compatibility molecular identification technology for two consecutive years, and it was determined to be a superior strain with self-fertility ability. Regional adaptability tests were performed in Changli, Laoting and Luannan counties in Hebei province from 2017 to 2019. The results were excellent, and it was finally examined, approved and named as Changhuazixia in 2020. The tree of Changhuazixia exhabits vigorous growth and strong branching ability, and the branches are relatively upright in angle. The first-year branches are brown in color and have long internodes. The leaves are long ovate in shape, with an average length of 17.4 cm and a width of 8.9 cm. The leaf surface is flat. There are 2 to 4 red kidney-shaped nectaries on the leaf stalk. The flower is white, and the relative position of petals (5-6) is overlapped, petals are oblate in shape, and stamens are slightly higher than pistil with more pollen grains. The fruit of Changhuazixia is kidney-shaped, with a purple-red skin, smooth surface, and red or purple-red flesh. The flesh is firm and has a sweet and sour flavor. The average single fruit mass is 9.6 g, with the maximum one up to 16.2 g. The soluble solids content is 20.5%, and the flesh is relatively firm, with a flesh firmness of 2.1 kg·cm-2. The soluble sugar content is 11.66%, the titratable acid content is 0.42%, and the sugar-acid ratio is 28.38. The edible rate is 93.4%. The fruit development period is 65 d, and it matures in late June in the Changli area of Hebei province (119°09′45″E, 39°43′07″N). Each flower bud contains 1 to 4 flowers, with an average diameter of 3.3 cm. There are 2 to 4 red kidney-shaped nectaries on the petiole. In the early fruiting stage, medium and long fruiting branches are the main fruiting branches. It bears fruit early and is highly productive, selffertile, and has strong continuous fruiting ability. It has strong stress resistance. It is suitable for cultivation in Hebei province and similar regions. It begins to flower and bear fruit in the third year and reaches high productivity in the fourth year. The yield of quinquennial and septennial grafted plants is 746.7 kg and 850.7 kg per 666.7 m2, respectively. Changhuazixia has a wide adaptability, it has better stress resistance, such as strong barren tolerance, cold resistance, and resistance to leaf spot disease and early defoliation disease. For cultivation techniques, the spacing between trees and between rows is 2 m × 5 m, and summer pruning should be emphasized for balancing tree vigor and promoting fruiting. Changhuazixia is a good cultivar and suitable for planting inside the Hebei area, and was certified (Register No: Ji S-SV-CA-014-2020) by the Evaluation Committees of Hebei Province in 2020.